Chiral secondary amino acids, their importance, and methods of analysis - Zahradníčková, Helena; Opekar, Stanislav; Řimnáčová, Lucie; Šimek, Petr; Moos, Martin (Amino acids, 2022)
Naturally occurring secondary amino acids, with proline as the main representative, contain an alpha-imino group in a cycle that is typically four-, five-, and six-membered. The unique ring structure exhibits exceptional properties-conformational rigidity, chemical stability, and specific roles in protein structure and folding. Many proline analogues have been used as valuable compounds for the study of metabolism of both prokaryotic and eukaryotic cells and for the synthesis of compounds with desired biological, pharmaceutical, or industrial properties. The D-forms of secondary amino acids play different roles in living organisms than the L-forms. They have different metabolic pathways, biological, physiological, and pharmacological effects, they can be indicators of changes and also serve as biomarkers of diseases. In the scientific literature, the number of articles examining D-amino acids in biological samples is increasing. The review summarises information on the occurrence and importance of D- and L-secondary amino acids-azetidic acid, proline, hydroxyprolines, pipecolic, nipecotic, hydroxypipecolic acids and related peptides containing these D-AAs, as well as the main analytical methods (mostly chromatographic) used for their enantiomeric determination in different matrices (biological samples, plants, food, water, and soil).
Keywords: Chiral analysis; Peptides; Proline analogues; peptidy; Proline; stereoizomerie; Imino acids; Amino Acids; iminokyseliny; prolin; Imino Acids; Enantiomers; Stereoisomerism; D- and L-secondary amino acids; aminokyseliny